Quantitative and qualitative aspects of L1 (Swedish) and L2 (English) idiom comprehension - Karlsson, Monica (Studies in Second Language Learning and Teaching, 2013)
In the present investigation, 15 first term university students were faced with 80 context-based idioms in English (L2) and Swedish (L1) respectively, 30 of which were in the source domain of animals, commonly used in both languages, and asked to explain their meaning. The idioms were of varying frequency and transparency. Three main research questions were thus addressed: 1. How well do students master idioms in their L2 as compared to their L1? 2. How do (a) degrees of transparency, (b) idiom frequency and (c) the choice of source domain affect students’ L1 and L2 comprehension? 3. To what extent is context used when interpreting L1 and L2 idioms? Results show that while the frequency of an idiom does not appear to play a part in whether it is comprehended or not in either language, the degree of transparency is of great importance in students’ L2. Also, students make extensive use of context in their L2.